Pengembangan Sistem Informasi Manajemen Sertifikasi Keahlian di Fakultas Ilmu Komputer Universitas Brawijaya Malang - Vicky Anggara; Achmad Arwan; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Information Systems Management certification of expertise in the Faculty of Computer Science of Brawijaya University is a system that assists in managing certification of expertise related to bootcamp information, registration bootcamp, information certification, certification registration, distribution of modules Botcamp, announcement of bootcamp schedules and certifications, and selection instructor Bootcamp. In addition, the system also helps to keep data safe in database storage, thus minimizing lost or damaged data. The need for this system is obtained through an interview process with the stakeholders that are the skills Certification coordinator at the Faculty of Computer Science of Brawijaya University who became the admin actor of this system. Literature studies are also conducted to support the problem solving. Software architecture is designed using Unified Modelling Language (UML). Some software also used to build this system include Visual Studio Code 1.43.2, Visual Paradigm 16.0, XAMPP v 3.2.4. The system consists of 61 functional needs modelled into the use case diagram as well as the use case scenario as the base of the groove that can be run on this system. The design phase produces the design of the system to be built. The architecture design generates diagram sequences, diagram classes, and database designing. Tests are divided into three, unit testing, integration testing, and validation testing with all results valid.